2006
DOI: 10.1111/j.1440-169x.2006.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of planarian X‐ray‐sensitive stem cells by fluorescence‐activated cell sorting

Abstract: The remarkable capability of planarian regeneration is mediated by a group of adult stem cells referred to as neoblasts. Although these cells possess many unique cytological characteristics (e.g. they are X-ray sensitive and contain chromatoid bodies), it has been difficult to isolate them after cell dissociation. This is one of the major reasons why planarian regenerative mechanisms have remained elusive for a long time. Here, we describe a new method to isolate the planarian adult stem cells as X-ray-sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
325
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 242 publications
(334 citation statements)
references
References 35 publications
(31 reference statements)
9
325
0
Order By: Relevance
“…Partial X-ray irradiation experiments demonstrated that stem cells located in any part of the body can rescue different irradiated body parts, suggesting that stem cells may have equivalent pluripotentiality. Recently, we have purified X-ray-sensitive cells using fluorescence-activated cell sorter (FACS) sorting and characterized them at the molecular and cellular levels (Hayashi et al 2006). These molecular and morphological analyses suggested both pluripotency and heterogeneity of the planarian stem cells (Higuchi et al 2007).…”
Section: Pluripotent Stem Cells In Planariansmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial X-ray irradiation experiments demonstrated that stem cells located in any part of the body can rescue different irradiated body parts, suggesting that stem cells may have equivalent pluripotentiality. Recently, we have purified X-ray-sensitive cells using fluorescence-activated cell sorter (FACS) sorting and characterized them at the molecular and cellular levels (Hayashi et al 2006). These molecular and morphological analyses suggested both pluripotency and heterogeneity of the planarian stem cells (Higuchi et al 2007).…”
Section: Pluripotent Stem Cells In Planariansmentioning
confidence: 99%
“…Studying brain regeneration in planarians may provide unique information enabling the generation of a brain from mouse or other vertebrate ES cells in vitro in the near future. For this purpose, we are attempting to purify both brain neurons and pluripotent stem cells from planarians using FACS (Asami et al 2002;Hayashi et al 2006), and to clarify whether pluripotent stem cells differentiate into neurons directly, or indirectly via a neural stem cell state .…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Under the light microscope, neoblasts appear as small round or ovoid cells scattered throughout the mesenchymal space (Orii et al, 2005;Sá nchez-Alvarado and Kang, 2005;Hayashi et al, 2006). Numerous electron microscopy studies have shown that neoblasts possess a relatively large nucleus and limited cytoplasm, which contains a high concentration of ribosomes, but little or no endoplasmic reticulum and only a few mitochondria (Hay and Coward, 1975;Morita et al, 1976;Hori, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently [17,19] the state of the art for neoblast isolation consisted in the dissociation of whole planarians in a medium free of calcium and magnesium, and then serial passage of this cell suspension through Nytex sieves of different pore diameters (160, 100, 60, 40 and 10 μm) [20]. Since neoblasts range between 5-8 μm in diameter, the fraction obtained after passage through the last sieve (10 μm) is rich in neoblasts (∼70%).…”
Section: Improving the Isolation Of Neoblastsmentioning
confidence: 99%
“…However this fraction is usually contaminated with a variety of cells (gastric and muscle cells as well as some neurons) that due to their geometry will sometimes pass through the 10 m filter. Agata and colleagues have improved on the methods to purify isolated neoblasts by developing fluorescence activated cell sorting (FACS) methods suitable for planarian cells [19].…”
Section: Improving the Isolation Of Neoblastsmentioning
confidence: 99%